2020
DOI: 10.1103/physrevd.101.023510
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological information content in redshift-space power spectrum of SDSS-like galaxies in the quasinonlinear regime up tok=0.3hMpc1

Abstract: Clustering properties and peculiar velocities of halos in large-scale structure carry a wealth of cosmological information over a wide range of scales from linear to nonlinear scales. We use halo catalogs in a suite of highresolution N-body simulations to construct mock catalogs of galaxies that resemble the SDSS-like luminous early-type galaxies at three redshift bins in the range 0.15 ≤ z ≤ 0.7. To do this we include 10 nuisance parameters to model variations in halo-galaxy connections for each redshift bin;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 108 publications
2
62
0
Order By: Relevance
“…The galaxy distribution observed by spectroscopic surveys is modulated by the Doppler effect due to the line-ofsight peculiar velocities of galaxies, and exhibits characteristic anisotropies, called the redshift-space distortion (RSD) [14][15][16]. The RSD effect is useful to improve cos-mological constraints by breaking degeneracies between the cosmological parameters and uncertainties in galaxy bias relative to the underlying matter distribution [17]. In addition, since the RSD effect is a gravitational effect, it can be used, if precisely measured, to probe the strength of gravitational field in large-scale structure, which can be in turn used to test gravity theory on cosmological scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The galaxy distribution observed by spectroscopic surveys is modulated by the Doppler effect due to the line-ofsight peculiar velocities of galaxies, and exhibits characteristic anisotropies, called the redshift-space distortion (RSD) [14][15][16]. The RSD effect is useful to improve cos-mological constraints by breaking degeneracies between the cosmological parameters and uncertainties in galaxy bias relative to the underlying matter distribution [17]. In addition, since the RSD effect is a gravitational effect, it can be used, if precisely measured, to probe the strength of gravitational field in large-scale structure, which can be in turn used to test gravity theory on cosmological scales.…”
Section: Introductionmentioning
confidence: 99%
“…In order to exploit the full information from galaxy redshift surveys, we need a sufficiently accurate theoretical template that enables a high-fidelity comparison with the measured clustering statistics of galaxies to obtain a robust estimate of cosmological parameters. The linear theory of cosmological fluctuations, which has been in a remarkable success in CMB analyses, ceases to be accurate at k 0.1 hMpc −1 due to nonlinear effects of structure formation [17]. The standard approach to tackle this difficulty has been analytic prescriptions based on the perturbation theory of large-scale structure [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The level of consistency between BOSS DR12 data on galaxy clustering (Alam et al 2017) and Planck 2018 depends on the chosen method of data compression (Sánchez et al 2017, Loureiro et al 2019, Kobayashi et al 2020). Tröster et al (2020b showed that when employing the geometrical quantities α ⊥ and α the data are not in tension with the ΛCDM parameters of Planck 2018.…”
Section: Tension With Full Planck Datamentioning
confidence: 99%
“…The most notable manifestation of this tension is the 4.2σ (Riess et al 2021) difference in the value of the Hubble constant, H 0 , between distance ladder estimates and the early-Universe cosmic microwave background (CMB) probe Planck (Planck Collaboration et al 2020a). Moreover, late-Universe probes of the large-scale structure, such as weak gravitational lensing (WL) and galaxy clustering, prefer a lower amplitude of the growth of structure than Planck, with tension up to the 3.2σ level in the parameter S 8 = σ 8 Ω m 0.3 , where σ 8 is the standard deviation of matter density fluctuations in spheres of radius 8 h −1 Mpc today and Ω m is the matter density parameter (Alsing et al 2017, Joudaki et al 2017a, Loureiro et al 2019, Tröster et al 2020b, Kobayashi et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have tried to incorporate secondary halo parameters into an HOD framework to account for the effects of assembly bias. Halo concentration, for example, has been a popular secondary parameter Croton et al (2007a); Vakili & Hahn (2019); Kobayashi et al (2020); Wechsler & Tinker (2018); Paranjape et al (2015), although numerous recent studies have shown that the environment of the halos plays a significant role in determining the galaxy distribution (Hadzhiyska et al 2020a,c;Hadzhiyska et al 2021;Yuan et al 2020;McEwen & Weinberg 2018;Xu et al 2020;Salcedo et al 2020b,c;Abbas & Sheth 2007;Pujol & Gaztañaga 2014). There also have been multiple prescriptions for including the halo environment in the HOD model (McEwen & Weinberg 2018;Xu et al 2020;Salcedo et al 2020b,c;Yuan et al 2020;Hadzhiyska et al 2020b;Salcedo et al 2020a).…”
Section: Introductionmentioning
confidence: 99%